SEFT as an Effort to Overcome the Manifestations of Burnout Syndrome - Zakiyah, Ana (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
Burnout syndrome describes a response to chronic work-related stress. One of the techniques to overcome this is the Spiritual Emotional Freedom Technique (SEFT), which combines spiritual power and energy psychology. This study used a literature review with the PICOS framework. Article search using electronic databases: Google Scholar, Research Gate, PubMed, and Science Direct with the keywords "SEFT" OR "EFT" and "Burnout syndrome". The inclusion criteria in this literature review are articles published from 2016 to 2023, available in full-text form. Exclusion criteria: articles are only in the form of journal reviews, and papers are published in proceedings. Number of articles reviewed: 10. SEFT combines psychological energy and spiritual therapy by using the tapping method at several meridian points in the body. Improvement of physical and psychological complaints after the administration of SEFT psychotherapy is a form of mind-body gap healing. SEFT treats disruptions of the body's energy system to eliminate negative emotions